The Higher the Life Satisfaction, the Better the Psychological Capital? Life Satisfaction and Psychological Capital: A Moderated Mediation Model - Shan, Huanhuan; Ishak, Zahari; Fan, Liheng (Frontiers in Psychology, 2022)
The current research investigates the mediating effects of attachment avoidance and the moderating effects of rejection sensitivity on the links between relationship life satisfaction and psychological capital. This research applied the Experiences in Close Relationship Experience Scale, Rejection Sensitive Scale, Positive Psychological Capital Scale, and Life Satisfaction Scale among 999 Chinese young adults as subjects. The results presented that life satisfaction had a significant positive predictive effect on psychological capital. Mediation analysis of the present research showed that attachment avoidance mediated the association between life satisfaction and psychological capital. Furthermore, moderated mediation analysis indicated that rejection sensitivity moderates the link between life satisfaction and attachment avoidance (first stage moderation). Compared with low rejection sensitivity individuals, high rejection sensitivity individuals show more attachment avoidance under low life satisfaction. The research results help understand the relationship between life satisfaction and psychological capital from the perspective of rejection sensitivity theory and attachment theory and have implications for guiding college students towards strengthening psychological capital, weakening rejection sensitivity.